Incidence of host site complications in periocular full thickness skin grafts. Issue 2 (21st January 2005) - Leibovitch, I; Huilgol, S C; Hsuan, J D; Selva, D
Abstract : Aim: To evaluate the complications of periocular full thickness skin grafts (FTSG) in patients treated with Mohs' micrographic surgery (MMS) for periocular malignancy. Method: This prospective, multicentre case series included all patients in Australia treated with MMS for periocular malignancy followed by reconstruction with FTSG, who were monitored by the Skin and Cancer Foundation, between 1993 and 1999. The parameters recorded were patient demographics, reason for referral, histological classification of malignancy and evidence of perineural invasion, duration of tumour, site, recurrences prior to MMS, preoperative tumour size, and postoperative defect size. FTSG donor sites included upper lid, preauricular, retroauricular, inner brachial, and supraclavicular. The primary outcome measures were FTSG host site complications (partial/complete graft failure, graft infection, acute bleeding/haematoma, graft hypertrophy, and graft contracture). Results: 397 patients (229 males, 168 females), mean age 60 (SD 15) years (range 20–91 years). 92.7% were diagnosed with basal call carcinoma, 2.0% with Bowen's disease, and 3.3% with squamous cell carcinoma. Medial canthus was involved in 66.5% of patients, lower eyelid in 28.0%, and upper eyelid in 5.5%. Postoperative complications were recorded in 62 patients (15.6% of all patients), and consisted of graft hypertrophy (45.1% of complications), graft contraction (29.1%), and partial graft failure (12.9%). The only statistically significant association found was a higher rate of graft hypertrophy in medial canthal reconstruction (p = 0.007). Conclusion: Host site complications of periocular FTSG are not common. Graft hypertrophy accounted for most complications and was more common in the medial canthal area. No other variables such as patient demographics, tumour characteristics, or donor site factors were associated with a higher risk of complications.